A Systematic Review of Tissue Engineering Scaffold in Tendon Bone Healing in vivo - Mao, Zimu; Fan, Baoshi; Wang, Xinjie; Huang, Ximeng; Guan, Jian; Sun, Zewen; Xu, Bingbing; Yang, Meng; Chen, Zeyi; Jiang, Dong; Yu, Jiakuo (Frontiers in Bioengineering and Biotechnology, 2021)
Abstract： Background: Tendon-bone healing is an important factor in determining the success of ligament reconstruction. With the development of biomaterials science, the tissue engineering scaffold plays an extremely important role in tendon-bone healing and bone tissue engineerin. Materials and Methods: Electronic databases (PubMed, Embase, and the Web of Science) were systematically searched for relevant and qualitative studies published from 1 January 1990 to 31 December 2019. Only Original articles that met eligibility criteria and evaluated the use of issue engineering scaffold especially biomaterials in tendon bone healing in vivo were selected for analysis. Results: The search strategy identified 506 articles, and 26 studies were included for full review including 2 human trials and 24 animal studies. 15 studies only used biomaterials like PLGA, collage, PCL, PLA, PET as scaffolds to repair the tendon-bone defect, on this basis, the rest of 11 studies using biological interventions like cells or cell factors to enhance the healing. The adverse events hardly ever occurred, and the tendon bone healing with tissue engineering scaffold was effective and superior, which could be enhanced by biological interventions. Conclusion: Although a number of tissue engineering scaffolds have been developed and applied in tendon bone healing, the researches are mainly focused on animal models which are with limitations in clinical application. Since the efficacy and safety of tissue engineering scaffold has been proved, and can be enhanced by biological interventions, substantial clinical trials remain to be done, continued progress in overcoming current tissue engineering challenges should allow for successful clinical practice.